IMPROVING THE USE OF INVESTMENTS IN THE SUSTAINABLE DEVELOPMENT OF AGRICULTURE - Xolmatov Sanjarbek Xojimamatovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article reveals the essence of the concepts of “sustainable development”, “sustainable development of agriculture”, “sustainable investment”. The current state of agriculture in the Andijan region, investments in fixed capital of the industry are considered. Proposals for sustainable development of agriculture are given.